Causes and management of tongue bite in primary care - Tina Chowdhary; Raman Kumar (Wolters Kluwer Medknow Publications, 2023)
Tongue bite typically refers to an injury to the tongue caused by accidental biting. While it may not be a severe medical emergency, it can cause discomfort and pain. Tongue biting can occur for various reasons, and it is often an accidental and involuntary action. While many tongue bites are minor and can be managed at home, severe or recurrent cases may require a visit to a healthcare professional or dentist for further evaluation. Depending upon the severity of injury, treatment may require first aid to hospital care. In family practice, primary care providers may encounter patients who present with complaints related to tongue bites. Majority of the tongue bite cases can be managed in the community setting itself, however few may require referrals those with severe injury and associated comorbidities such as seizure. Taking preventive measures can help reduce the likelihood of future incidents. Paying attention to situations or habits that may contribute to tongue biting, such as stress, nervous habits, or certain dental issues may be advised to the patients.